IMPLEMENTASI KEBIJAKAN FREE TRADE ZONE (KAWASAN PERDAGANGAN BEBAS DAN PELABUHAN BEBAS) DI KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU (Studi Kasus : Peredaran Rokok Khusus Free Trade Zone) - Pradito Sony W (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2018)
The objective of the research is to know and analyze the Implementation of Free Trade Zone Policy (Free Port of Free Port) in Bintan Regency of Kepulauan Riau Province. The research method used is descriptive research method, with qualitative approach. Data obtained through data collection techniques: interviews and documentation. The results showed that the Implementation of Free Trade Zone (FTZ) Policy In Bintan Regency, Kepulauan Riau Province has not been good. : Standard and FTZ standard clarity in FTZ Special Cigarette Distribution is very clear and has also been supported and integrated with various other programs. Resources in the implementation of FTZ policy in FTZ Special Cigarette Distribution are still inadequate, both financial resources and human resources. Relationship between Ftz policy implementing organizations in FTZ Special Cigarette Circulation is still weak Tactics involved incidental and unscheduled. The characteristics of implementing organizations are quite supportive for the implementation of Ftz policy in FTZ Special Cigarette Distribution. The current social and political conditions are sufficient to support economic conditions not fully supporting the implementation of FTZ policy in FTZ Special Cigarette Distribution. The Implementator is sufficiently aware of the policy implementation policy in FTZ in the FTZ Special Cigarette Distribution. Bintan Registration Agency and Customs and Excise Agency have prioritized customer satisfaction.Keywords: Implementation, Policy, and Free Trade Zone